Causes of Self-Censorship in the Japanese Mass Media - Andre Yeshammah Wicaksono; Andy Bangkit Setiawan (International Forum of Researchers and Lecturers, 2023)
This study analyzes the causes of self-censorship in the Japanese mass media. Japan is now considered a country that has low press freedom. Approved by PM Koizumi`s cabinet in 2002 against a bill banning excessive reporting activities which caused strong protests from newspapers and broadcasters. The purpose of this research is to explain the causes of self-censorship in the Japanese mass media. This study uses qualitative research methods with the Thematic Analysis Approach approach and model of analysis data taken in The Journalist series. The conclusion of this study is that the Japanese mass media exercise self-censorship due to pressure from outsiders which makes it difficult for them to present the news and sources who refuse to be interviewed.